Rural Industry and Its Social Foundation in the Integrated Urban-Rural Development Process: A Case Study of Processing in Remote Villages under the Jurisdiction of City L, Zhejiang Province. (2nd July 2020) - Wei, Fu
Abstract : Rural industry provides an important basis for rural revitalization, and its development can promote urban-rural integration. Rural China has long had complex and diverse rural industries whose existence and development is founded on rural society. Complex and varied rural industries have long existed in rural China, where local society provides the social foundation for their existence and development. One example is the processing of supplied materials or putting-out system ( lailiao jiagong 来 料 加 工 ) in remote rural areas under the jurisdiction of City L, Zhejiang. In recent years, industries in the developed areas of Zhejiang have expanded to remote villages through processing to order, driving the growth of rural industries in remote areas. The processing of supplied materials is a link in the global production chain. Flexible decentralized processing links surplus rural labor in remote areas to the vast global market. The industry's production process is deeply embedded in local society; interpersonal relationships and social ethics facilitate production management, forming a social foundation for the development of rural industry. Social ethics in these areas takes the particular operational form of sensitive cultivation of personal relationships or "human feelings." The processing of supplied materials has shaped the distinctive character of rural development and provides a route for social transformation. To implement the strategy of rural revitalization, besides provision of land, finance and industrial policy, China needs to handle the social foundation of rural areas rationally, make full use of rural social resources and stimulate endogenous motivation in rural society.